Toxinological characterizations of the venom of hump-nosed pit viper (Hypnale hypnale) / Tan Choo Hock - Tan, Choo Hock (2013)
Hump-nosed pit viper (Hypnale hypnale) is a medically important snake in Sri Lanka and Western Ghats of India. Envenomation by this snake still lacks effective antivenom clinically. The species is also often misidentified, resulting in inappropriate treatment. The median lethal dose (LD50) of H. hypnale venom varies from 0.9 μg/g intravenously to 13.7 μg/g intramuscularly in mice. The venom shows procoagulant, hemorrhagic, necrotic, and various enzymatic activities including those of proteases, phospholipases A2 and L-amino acid oxidases which have been partially purified. The monovalent Malayan pit viper antivenom and Hemato polyvalent antivenom (HPA) from Thailand effectively cross-neutralized the venom’s lethality in vitro (median effective dose, ED50 = 0.89 and 1.52 mg venom/mL antivenom, respectively) and in vivo in mice, besides the procoagulant, hemorrhagic and necrotic effects. HPA also prevented acute kidney injury in mice following experimental envenomation. Therefore, HPA may be beneficial in the treatment of H. hypnale envenomation. H. hypnale-specific antiserum and IgG, produced from immunization in rabbits, effectively neutralized the venom’s lethality and various toxicities, indicating the feasibility to produce an effective specific antivenom with a common immunization regime. On indirect ELISA, the IgG cross-reacted extensively with Asiatic crotalid venoms, particularly that of Calloselasma rhodostoma (73.6%), suggesting that the two phylogenically related snakes share similar venoms antigenic properties. Doublesandwich ELISA was specific and able to distinguish and quantify venoms of H. hypnale, Daboia russelii and Echis carinatus sinhaleyus (three common Sri Lankan viperids) in human sera; hence it may be useful in diagnostics and venom level monitoring especially during clinical studies. In rabbits, the venom when injected intravenously showed a rapid distribution phase (t1/2α = 0.6 h) and a slow elimination phase (t1/2β = 20 h), consistent with prolonged abnormal hemostasis reported. The intramuscular bioavailability was exceptionally low (Fi.m = 4%), accountable for the highly varied LD50 between intravenous and intramuscular envenomings in animals. HPA infused post-envenomation markedly reduced the serum venom levels and subsequently induced venom redistribution. The redistributed venom was completely neutralized by a second dose of HPA. Proteomic study by shotgun-liquid chromatography-mass spectrometry/mass spectrometry (shotgun-LC-MS/MS) revealed 52 proteins in the venom, 70% of which are toxinologically related. The combined use of reverse-phase high performance liquid chromatography, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, peptide sequencing and mass fingerprinting technologies enabled the identification of the venom major components, i.e. zinc-dependent metalloproteases, phospholipases A2, Lamino acid oxidases, serine proteases and C-type lectins. These toxins correlate with the venom’s principal effects: hematoxicity (hemorrhage, coagulopathy) and tissue destruction (necrosis). Understanding of the venom composition is essential for ascertaining the principal toxins, and for optimizing antivenom formulation. Furthermore, hypnobin, a 37 kDa thrombin-like enzyme was purified. It exhibits arginine esterese and amidase activities, besides distinct specificity towards different mammalian fibrinogens. In fibrinogen coagulation, hypnobin predominantly releases fibrinopeptide A, followed slowly by a small amount of fibrinopeptide B. The findings provide insights into the structures and mechanism of the thrombin-like enzyme, which are important for elucidation of the pathophysiology and for potential drug discovery, e.g. an anticoagulant for thromboembolic disorders.